Estudo da análise vibrações em equipamentos rotativos para melhoria da confiabilidade na indústria de papel e celulose - Cussolim, Guilherme de Faria [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
With the development of this work, it is expected the dissemination of the best practices of maintenance of the paper and pulp market for the whole community. Maintenance models are studied as well as the forms of their management. To elucidate the knowledge, a case study is also presented on how to perform two specific types of maintenance, predictive and preventive maintenance. Installed in the interior of the state of São Paulo, the production unit studied produces 1200 tons of paper per day and includes in its facilities more than 100 thousand equipment that demands maintenance and daily operational care based on vibration analysis as the main tool of situational diagnosis. The economic importance of this knowledge is given in the comparison of the results of the application of the different maintenance in the same equipment where the impacts are translated into financial values, availability of production and reliability. Given the proportions, this study is applicable to any type of production industry, since the focus is kept on maintenance and its case study is a critical look at the effects of choosing the moment and form of the application and the consequences thereof of the same

Com o desenvolvimento deste trabalho é esperado a difusão das melhores práticas de manutenção do mercado de papel e celulose para toda a comunidade. São estudados modelos de manutenção bem como as formas de sua gestão. Para elucidar os conhecimentos, é apresentado também um estudo de caso sobre como é a realização de dois tipos específicos de manutenção, a manutenção preditiva e corretiva. Instalada no interior do estado de São Paulo, a unidade de produção estudada produz 1200 toneladas de papel por dia e contempla em suas instalações mais de 100 mil equipamentos que demandam manutenção e cuidados operacionais diários que usam como base a análise de vibrações como principal ferramenta de diagnóstico situacional. A importância econômica deste conhecimento é dada na comparação dos resultados da aplicação das diferentes manutenções em um mesmo equipamento onde os impactos são traduzidos em valores financeiros, disponibilidade de produção e confiabilidade. Guardada as proporções, este estudo é aplicável à qualquer tipo de indústria de produção, uma vez que o foco é mantido em manutenção e seu estudo de caso é de um olhar crítico sobre os efeitos da escolha do momento e forma da aplicação e as consequências decorrentes da mesma
Study of vibration analysis in rotary equipment for reliability improvement in the pulp and paper industry
Keywords: Manutenção produtiva total; Vibração - Medição; Confiabilidade (Engenharia); Papel - Industria; Vibration Measurement